Peran Guru Pendidikan Agama Islam (PAI) dalam Upaya Pembentukan Karakter Disiplin dan Tanggung Jawab Anak SMP - Anwar, Mohammad Shohibul (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2021)
This thesis discusses the role of the teacher (PAI) in an effort to shape the character of discipline and responsibility of children at SMPN 1 Astanajapura. The purpose of this study was to find out: what is the role of Islamic Education teachers in the effort to form disciplinary character, what is the role of Islamic Education teachers in the effort to build the character of responsibility, and the supporting and inhibiting factors in the effort to form the character of discipline and responsibility in the school. This research is a qualitative descriptive study. The research subjects are the principal, student staff, teachers, and students. Data collection was carried out by observation, interviews, and documentation study. The results showed that Islamic education teachers in the effort to form the character of discipline and responsibility showed their roles, namely: the role of an educator, the role of a model and role model, and the role as a motivator. In the effort to build this character, there are supporting and inhibiting factors in its implementation. Supporting factors come from teachers, parents, the environment. Then the inhibiting factor comes from peers.